Influence of fire on woody vegetation density, cover and structure at Tiisa Kalahari Ranch in western Botswana. (11th December 2015) - Mudongo, Edwin; Fynn, Richard; Bonyongo, Mpaphi Casper
Abstract: Woody vegetation assessments were conducted in the burned and unburned paddocks of Tiisa Kalahari Ranch in western Botswana to determine the influence of opportunistic burning on woody species density, cover and structure in semiarid rangelands. Burning was conducted by farm management twice in one paddock in October 2005 and 2006, and once in another paddock in October 2011 to control bush encroachment. Sampling was conducted in May 2012 using 50 by 2 m transects (16 at the 2011 burn site and 18 at the 2005/2006 burn site) as paired comparisons in both burned and unburned paddocks. Tree height was 0.27 m (28%) and 0.23 m (21%) lower ( P  <   0.05) in burned paddocks at the 2011 and 2005/2006 burn sites, respectively. There was an increase in the proportion of saplings and a decrease in tall woody plants in burned areas at all sites ( P  <   0.001). At the 2011 burn site, height and cover of Catophractes alexandri were 63% ( P  =   0.041) and 67% ( P  =   0.035) lower in burned paddocks, respectively. Density of Acacia mellifera was 53% ( P  =   0.031) lower, with more multi‐stemmed (>20 stems) plants in burned paddocks ( P  =   0.02). Grewia flava density was 59% higher in burned paddocks ( P  =   0.038). At the 2005/2006 burn site both height and density of Acacia hebeclada were significantly higher in burned paddocks (65%, P  =   0.045 and 56%, P  =   0.037, respectively). Tarchonanthus camphoratus was only present at this site, where its height, density and cover were significantly lower in burned paddocks ( P  <   0.05). Overall, tree height was shorter in burned than unburned paddocks, with C. alexandri contributing the most to the height reduction. Follow up browsing by goats on the coppice growth after burning may prevent C. alexandri, a dominant encroaching species from recruiting and spreading.